Intertwining the classical and modern receptions of astrology - Nicholson, Stephanie (My University, 2017)
The purpose of this research paper is to explore the relationship between the classical reception on astronomy and the modern practices of astrology. Specifically to Greek and Roman mythology, the results of this paper illuminate the connection between ancient practices of astronomy and today's knowledge of astrology. From all the evidence presented on these ideas, and their associations with Greek and Roman mythology, it becomes apparent in this paper that these ancient concepts about the stars, planets, time and the seasons all deeply intertwine and connect to the present-day knowledge of astrology.
Keywords: Greek mythology; Roman mythology; astrology